Effect of Neocortical and Hippocampal Amyloid Deposition upon Galaninergic and Cholinergic Neurites in AβPPswe/PS1ΔE9 Mice - Kelley, Christy M. (2011)
Amyloid-β (Aβ) plaques occur in close apposition to thickened or swollen cholinergic and galaninergic neurites within the neocortex and hippocampus in Alzheimer’s disease (AD). Despite this observation, the effect of Aβ deposition upon cholinergic and galaninergic dystrophic neurite formation remains unclear. Therefore, the purpose of this study was to evaluate the interaction between Aβ deposition within the neocortex and hippocampus upon cholinergic and galaninergic dystrophic neurite formation. Neocortical and hippocampal tissue harvested from 3- and 12-month-old amyloid-β protein precursor (AβPP)(swe)/PS1ΔE9 transgenic (tg) mice were dual-immunolabeled with antibodies against either choline acetyltransferace (ChAT) and Aβ (10D5) or galanin (Gal) and Aβ. Stereology was used to quantify amyloid plaques and cholinergic or galaninergic dystrophic neurites. Plaque number was assessed using the optical fractionator; plaque area was calculated with the Cavalieri estimator, and dystrophic neurite numbers and thickness were manually measured. Neither amyloid nor dystrophic neuritic profiles were seen in the brains of 3-month-old tg mice. In contrast, quantitative analysis revealed significantly more plaques in neocortex than hippocampus, with no difference in regional plaque size in 12-month-old tg mice. Significantly more cholinergic than galaninergic dystrophic neurites-per-plaque occurred in the neocortex and hippocampus. Additionally, cholinergic dystrophic neurites were thicker than galaninergic dystrophic neurites in both regions. These data suggest that amyloid plaque deposition has a greater impact upon cholinergic than galaninergic dystrophic neurite formation in the neocortex and hippocampus in AβPP(swe)/PS1ΔE9 tg mice. These data are also compatible with the hypothesis that galanin is neuroprotective and reduces dystrophic neurite formation in the face of amyloid toxicity.